Advertising media planning. - Sissors, Jack Z., ....-; Baron, Roger B., ....- (London : McGraw-Hill, 2010)
The industry standard for 30 years-updated to include the newest developments in digitization and the three screens of video Apply the latest advertising technologies Build your brand in every medium Create the right budget for each campaign Through six previous editions, Advertising Media Planning has proven essential to the success of both practicing and aspiring media planners. Now in its seventh edition, it continues to provide valuable insight into the construction of media plans that most effectively achieve marketing objectives. Advertising Media Planning, seventh edition, retains all the critical information you need to know about traditional media-including TV, radio, and print--while exploring the latest media forms, illustrated with major advertiser case histories. You'll find comprehensive coverage of the latest media planning and digital technologies, including: - Organic and sponsored Google search - Digital out-of-home video - Internet banners - Computerized media channel planning - Cell phone mobile-media - DVR's impact on TV commercial viewing - New online and traditional media measurement technologies - Interactive television - Cross-media planning - Data fusion - International competitive spending analysis This is an exciting time for media planners. Those with the most creativity, strategic insight, and knowledge of the market are sure to find the greatest rewards. Providing firm grounding on the fundamentals and bringing you up to speed on the latest developments in digitization, this updated classic is the best and most complete companion available for navigating the new frontier of media planning.
Keywords: Go international; International office; Reclame